Diversionary Measures as Response of Society to Juvenile Crime in Croatia and Serbia - Ivan Joksić; Jelena Matijašević Obradović (Zbornik Radova Pravnog Fakulteta u Splitu, 2017)
In every society there are individuals or organized groups who openly or covertly violate social norms that prescribe what behavior patterns. The danger of such actions is reflected in the presence of negative tendencies in the field of further social disorganization. It is known that often the criminality of juveniles become known only when it is necessary to apply repressive sanctions that include a number of limitations. Given the fact that the sentence was dominated as a criminal sanction social reaction to crime youth was purely punitive character. There for, the same types of punsihment are applied on juveniles with certain restrictions relating to the lenient punishment and much more liberal regime of imprisonment. In such a situation society failed to achieve a more serious influence on the improvement of the status of minors and their full integration into their courses. Further development of the social and legal awareness contributed to the discovery of new forms of no / penal response. In this regard, diversion measures represent the first and right step on the road to improving juvenile offenders committed offenses in particular the fulfillment of certain conditions. The overall trends of harmonization of domestic legislation with comparative and international and regional, mostly European instruments, countries of ex-Yugoslavia incorporated in their legislation for the imposition of diversionary measures. Taking into account the planned scope of work the authors have chosen Croatia and Serbia, which are each in their own way, first spelled out, and then with great difficulty started with sporadic use of diversionary measures.